Pemodelan Numerik Kekuatan Pintu Air Baja - Fitriansyah Fitriansyah; Miftahul Iman; Aminullah Aminullah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The intake building for Embung Sei Bubu had been designed to be an open channel with the flood gate. The flood gate had been designed from steel with a net width of 1.35 m and the height of the door opening is 0.0076 m. The corrosion is one of the hazardous threat to the strengthness and durability of the flood gate. This research numerically models flood gate that was attacked by pitting corrosion. The pitting corrosion had been modelled in several small holes randomly were distributed on the surface of the flood gate, precisely on the surface of the water. The numerical modeling had been performed in finite element method utilized computer programs such Abaqus. The results showed there was a reduction in the capacity of the steel flood gate due the hole increasing. The reduction in stress capacity had been indicated by the stress concentration that was occured around the pitting corrosion. The stress reduction occured with the change in the percentage of pitting corrosion distribution area of ​​10% (225 MPa), 20% (175 MPa) and 30% (120 MPa)